ANALISIS DATA KUALITATIF DALAM EVALUASI KURIKULUM PROGRAM STUDI SARJANA PENDIDIKAN AGAMA ISLAM DI KALIMANTAN TIMUR - Muhamad Fajri; Zurqoni Zurqoni; Sugeng Sugeng (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2023)
Islamic Religious Education is an undergraduate education study program, intended as a teacher training program. Teacher quality can also be influenced by the curriculum followed by the Religion teacher during his undergraduate studies. Evaluation of the curriculum of the Islamic Religious Education Study Program is an interesting matter to discuss about qualitative data collection techniques. The purpose of this research is to analyze and find out the qualitative data analysis techniques used in the Islamic Religious Education Study Program and the analytical procedures at each tertiary institution in East Kalimantan. The results of this study indicate that the Islamic Religious Education study program at tertiary institutions in Samarinda City and Kutai Kartanegara Regency both use descriptive methods in obtaining qualitative data when evaluating their curriculum, especially on learning items. Then the analysis technique used for the descriptive data is qualitative data analysis of the Milles, Hubarmen and Saldana interactive model, while the City of Balikpapan uses content analysis, because it uses data in the form of documents as single data.